THE EFFECTIVENESS OF USING DISCUSSION METHOD IN TEACHING WRITING DESCRIPTIVE TEXT AT 10th ADMINISTRASI PERKANTORAN GRADE 1st SEMESTER IN SMKN 1 SUBANG - RA SANTIANI KARINA (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN, 2016)
Nowadays, writing lead people getting success, but some people says is hard, but for the rest is easy, is needed collaborate between who is told hard and easy one. So, discussion method is one of a way, because when work on the group it will be help and suggest. Population on this research is all of students’ X Administrasi Perkantoran (AP) SMKN 1 Subang and the sample are X AP 1 as control class and X AP 3 as experiment class. The result of this research with using Mann-Whitney test is there is no the effectiveness using discussion method on writing descriptive text.